Wire Lost During Central Venous Catherization Insertion: A Case Report - Azalia, Talitha; Mahmud, Mahmud; Yudho Pratomo, Bhirowo; Rizki Ilahi, Oktavian (Riviera Publishing, 2025)
Central venous catheterization (CVC) is a common procedure, yet it carries a risk of rare, preventable, and serious complications, such as guidewire loss, which can lead to severe morbidity and mortality. This case report aims to describe the occurrence, multidisciplinary management, and successful retrieval of a lost guidewire during an emergency CVC insertion. We report the case of a 63-year-old male with a subarachnoid hemorrhage. During CVC placement via the right femoral vein under ultrasound guidance, the guidewire was accidentally advanced into the central circulation and lost. A multidisciplinary team decided on endovascular retrieval. The retained guidewire was successfully retrieved three days later in the catheterization lab using a snaring technique, without any procedural complications. Unfortunately, the patient later died due to the progression of his primary neurological injury, underscoring that while the iatrogenic complication was resolved, the outcome was determined by the underlying critical illness. Guidewire loss is a preventable complication. Strict adherence to procedural protocols, especially in emergencies, early recognition, and prompt multidisciplinary coordination are crucial. Endovascular intervention is a safe and effective therapeutic option for managing this serious iatrogenic event.